2001
DOI: 10.1016/s0092-8674(01)00609-2
|View full text |Cite
|
Sign up to set email alerts
|

Meiotic Silencing by Unpaired DNA

Abstract: The silencing of gene expression by segments of DNA present in excess of the normal number is called cosuppression in plants and quelling in fungi. We describe a related process, meiotic silencing by unpaired DNA (MSUD). DNA unpaired in meiosis causes silencing of all DNA homologous to it, including genes that are themselves paired. A semidominant Neurospora mutant, Sad-1, fails to perform MSUD. Sad-1 suppresses the sexual phenotypes of many ascus-dominant mutants. MSUD may provide insights into the function o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
553
3
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 409 publications
(569 citation statements)
references
References 47 publications
12
553
3
1
Order By: Relevance
“…This phenomenon has been termed meiotic silencing by unpaired DNA (MSUD) and shown to require an RdRP (Sad1) and an Argonaute-like protein (Lee et al 2003;Shiu et al 2001). MSUD also requires RNA production from the unpaired DNA sequence and these transcripts are presumable used as a template by Sad1 to synthesize dsRNA that enters the degradative RNAi pathway Matzke and Birchler 2005;Nakayashiki 2005).…”
Section: Additional (Derived?) Functions Of the Rnai Machinerymentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon has been termed meiotic silencing by unpaired DNA (MSUD) and shown to require an RdRP (Sad1) and an Argonaute-like protein (Lee et al 2003;Shiu et al 2001). MSUD also requires RNA production from the unpaired DNA sequence and these transcripts are presumable used as a template by Sad1 to synthesize dsRNA that enters the degradative RNAi pathway Matzke and Birchler 2005;Nakayashiki 2005).…”
Section: Additional (Derived?) Functions Of the Rnai Machinerymentioning
confidence: 99%
“…For instance, putative homologs of a tomato RdRP are required for post-transcriptional gene silencing (PTGS) triggered by sense transgenes in A. thaliana, for quelling (a phenomenon similar to PTGS) and for meiotic silencing by unpaired DNA in Neurospora crassa, as well as for RNAi in C. elegans and Dictyostelium discoideum (Baulcombe 2004;Cogoni and Macino 2000;Martens et al 2002;Shiu et al 2001;Sijen et al 2001;Wassenegger and Krczal 2006). It has been proposed that RdRPs generate dsRNA from single-stranded transcripts either by de novo, primer independent second-strand synthesis (utilizing as template "aberrant" RNAs, presumably lacking normal processing signals such as a 5′ cap or a polyA tail) or by using siRNAs as primers to synthesize RNA complementary to the target mRNA (Baulcombe 2004;Sijen et al 2001;Wassenegger and Krczal 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Homozygous seeds produced by a hemizygous parent contain heavily methylated cytosines, at symmetrical as well as nonsymmetrical positions, in the region between the T-DNA insertion and the ATG codon. In the haploid Neurospora crassa, a gene not paired with its homologue in prophase I of meiosis forms a DNA loop, initiating Meiotic Silencing by Unpaired DNA (MSUD) (Shiu et al, 2001;Lee et al, 2004). This loop is detected and leads to a transient silencing by a posttranscriptional mechanism of all homologous sequences, including those that are themselves paired.…”
Section: Discussionmentioning
confidence: 99%
“…In mammals, it was observed that DNA lacking a partner during meiosis, such as the X chromosome in males, could be silenced by histone methylation (Bean et al, 2004) indicating that the genetic imprinting of individual loci or whole chromosomes was established during gametogenesis. In the haploid fungus Neurospora crassa, it was shown that a gene unpaired from its homologue during meiosis, could induce the silencing of all homologous sequences by a process named Meiotic Silencing by Unpaired DNA (MSUD) (Shiu et al, 2001;Shiu and Metzenberg, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Many early studies focused on mutation and mutability (De Serres & Kolmark 1958; De Serres & Brockman 1999) and, for example, the reference genome strain is called “Oak Ridge” reflecting its origins as a model organism for the study of low-dose radiation at the Atomic Energy Commission (a predecessor to the current US Department of Energy) Oak Ridge National Laboratory (Kafer 1982). As a model for cell biology and physiology, Neurospora has allowed significant impact in understanding of genome defence through vegetative gene silencing (Fulci & Macino 2007), meiotic gene silencing (Shiu et al 2001; Shiu & Metzenberg 2002), mutation of repeated DNA during meiosis (Selker & Garrett 1988; Cambareri et al 1991), and overall epigenetic gene regulation (Cambareri et al 1996; Selker et al 2003; Aramayo & Selker 2013). As a model for molecular physiology, it has been one of the leading models for analysis of the endogenous circadian rhythm (Baker et al 2012).…”
Section: Introductionmentioning
confidence: 99%